PENGARUH PENDAPATAN DAN BEBAN TERHADAP LABA PADA PT. ANUGRAH ABADI BARU) - Linda Aryani; Yudiana Yudiana; Rahmad Mulyana Dali (JURNAL PUNDI, 2023)
This study aims to determine the effect of the company's income and expenses on profits at PT. Anugrah Abadi Baru. The data collection technique used in this study is secondary data because the data obtained are in the form of documents, information and annual income statement data for the period 2014 to 2021 which are obtained from the financial statements of PT. Anugrah Abadi Baru. This type of research is quantitative. . Based on multiple regression test of Y = -6655237851.160 + 0.186 X1 – 0.683X2 + e. The results of the t-test income t-count 2.736 > t table 2.571, t-test on the load where there is an influence between the t-count 2.844 > t table 2.571 which means Ho 1 is rejected and Ha 1 is accepted, it can be concluded that income and expenses partially (individual ) can affect earnings, based on the results of the f test simultaneously (together), significant X to Y is 0.025 < from 0.05, which means H1 is accepted, where there is a simultaneous effect on earnings. Based on the results of these data, it can be concluded that income and expenses affect the profit of PT. Anugrah Abadi Baru and the company can increase operating income and streamline expenses so as to achieve increased profits.